HUBUNGAN MOTIVASI DENGAN KEPATUHAN PASIEN BERBEKAM DI PUSAT PENGOBATAN HOMEOPATI AL JAWAD PEKANBARU - Kiki Parmanda (Jurnal Keperawatan Abdurrab, 2016)
Cupping is classic therapy method that have been used in many treatment and therapy of various health problem such as : blood disease / illness like hemopilia and hypertension, rheumatic like arthritis, sciatica/ back pain, migren, anxiety, other general illness and mental illness (Widharto, 2007). The purpose of this research is to understand the Relationship Between Motivation and Patience’s Cupping Compliance in Al Jawad Homeopati Care Center Pekanbaru. Kind of the research is Correlation Descriptive with Cross Sectional research method. Population of the research is all patients that’s enduring cupping therapy in Al Jawad Homeopati Care Center Pekanbaru. Research was held on February 23 rd until March 13th 2015 with 118 respondences. Understanding of sample is using questioner research instrument. The data that have been collected was processing and analizing with Ms Excell computer program and statistic program (SPSS) version 17.0. Analyse of data including univariate analysis with find out frequency distribution and bivariate analysis with Chi square test (p<0.05). Research result showed from 118 respondences, partly of total have high motivation that 23 respondences (50,0%) but the cupping compliance have only 48 respondences (66,7%). Depends on that SPSS statistic-correlation test, have been discovered (p= 0.107> 0.05) so Ho was accepted and Ha was denied. Means there’s no a relationship between motivation with cupping obediences/loyalty of respondences in Al Jawad Homeopati Care Center Pekanbaru.